2020
DOI: 10.1101/2020.11.17.387902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential ER stress and inflammatory responses are induced by SARS-CoV-2 ORF3 through ERphagy

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections have resulted in a number of severe cases of COVID-19 and deaths worldwide. However, knowledge of SARS-CoV-2 infection, diseases and therapy remains limited, underlining the urgency of fundamental studies and drug development. Studies have shown that induction of autophagy and hijacking of autophagic machinery are essential for infection and replication of SARS-CoV-2; however, the mechanism of this manipulation and function of autophagy du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
7
2
Order By: Relevance
“…We have explanations for five of the seven cases that diverge. Zhang, X. et al 41 shows that IFN-I is induced by expression of p3a, which the model cannot recapitulate, most likely as in our model NF-kB does not induce IFNs. Similarly, Thorne L. G. et al 43 found that inhibition of NF-kB with the IKK inhibitor TPCA-1 reduced IFN expression, a finding that is also not recapitulated by the model.…”
Section: Validating the Model Against Publicly Available Datacontrasting
confidence: 56%
See 3 more Smart Citations
“…We have explanations for five of the seven cases that diverge. Zhang, X. et al 41 shows that IFN-I is induced by expression of p3a, which the model cannot recapitulate, most likely as in our model NF-kB does not induce IFNs. Similarly, Thorne L. G. et al 43 found that inhibition of NF-kB with the IKK inhibitor TPCA-1 reduced IFN expression, a finding that is also not recapitulated by the model.…”
Section: Validating the Model Against Publicly Available Datacontrasting
confidence: 56%
“…We have explanations for five of the seven cases that diverge. Zhang, X. et al 41 shows that IFN-I is induced by expression of p3a, which the model cannot recapitulate, most likely as in our model NF-kB does not induce IFNs.…”
Section: Validating the Model Against Publicly Available Datacontrasting
confidence: 56%
See 2 more Smart Citations
“…During viral infection, ER is hijacked for entry to host cells and replication and assembly of viral genomes [30]. Emerging evidence suggests that coronavirus infection, including SARS and COVID-19, triggers ER stress that sequentially activates unfolded protein response and inflammatory reactions [31][32][33]. Indeed, besides the SEC62 and SGTB genes that degrade unfolded proteins in ER, the list of molecular risk factors contains four additional genes (UBE2J2, COPS5, MBTPS2, and PPIA) that respond to unfolded proteins.…”
Section: Discussionmentioning
confidence: 99%